1997
DOI: 10.1128/jcm.35.4.982-984.1997
|View full text |Cite
|
Sign up to set email alerts
|

Ability of commercial ligase chain reaction and PCR assays to diagnose Chlamydia trachomatis infections in men by testing first-void urine

Abstract: A total of 287 men (37.6% with symptoms of urethritis) attending a hospital-based sexually transmitted disease clinic had urethral swabs tested by culture and by direct fluorescent-antibody assay. First-void urine (FVU) was tested for Chlamydia trachomatis by commercially available ligase chain reaction (LCR) and PCR assays. By using an expanded reference standard, 35 men (12.2%) were found to be positive. By performing LCR and PCR, the infection prevalence was found to be approximately twice (11.5 and 12.2%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
11
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 15 publications
4
11
0
Order By: Relevance
“…While the manuscript was being prepared, two other studies reported similar results for the COBAS AMPLICOR test (14,26). These values are similar to those reported for the nonautomated AMPLICOR C. trachomatis test (2, 6, 25-28, 30, 35) and other amplificationbased C. trachomatis tests (1,6,7,9,14,18,23,25,26,30,33). Virtually identical performance was observed for urine and endocervical swab specimens from women.…”
Section: Discussionsupporting
confidence: 70%
“…While the manuscript was being prepared, two other studies reported similar results for the COBAS AMPLICOR test (14,26). These values are similar to those reported for the nonautomated AMPLICOR C. trachomatis test (2, 6, 25-28, 30, 35) and other amplificationbased C. trachomatis tests (1,6,7,9,14,18,23,25,26,30,33). Virtually identical performance was observed for urine and endocervical swab specimens from women.…”
Section: Discussionsupporting
confidence: 70%
“…While many studies have examined the sensitivity of LCR or PCR testing of urine specimens, we were able to find only four reports of direct comparisons of the LCR and Roche PCR tests in the literature. In three studies, there were no statistically significant differences between PCR and LCR analyses of (3,20) found that after freezing of the urine samples, the PCR detected additional positive samples. However, in our study, the urine samples were tested by PCR prior to freezing at Ϫ70°C until tested by LCR, yet the PCR test still performed better than the LCR.…”
mentioning
confidence: 98%
“…The use of nucleic acid amplification methods such as PCR has significantly improved our ability to diagnose genital Chlamydia trachomatis infections (3). These methods also allow for the use of noninvasive urine specimens for testing which are more acceptable to patients (3,5,10,11,15). The introduction of commercially available automated DNA amplification assays has allowed more laboratories to introduce these technologies for routine testing of specimens.…”
mentioning
confidence: 99%